Lorenzo de' Medici and the art of magnificence - Kent, F. W. (Francis William), 1942- (Johns Hopkins symposia in comparative history, 2004)
"Historian F.W. Kent offers a new look at Lorenzo's relationship to the arts, aesthetics, collecting, and building - especially in the context of his role as the political boss (maestro della bottega) of republican Florence and a leading player in Renaissance Italian diplomacy. Kent's approach reveals Lorenzo's activities as an art patron as far more extensive and creative than previously thought. Known as "the Magnificent," Lorenzo was broadly interested in the arts and supported efforts to beautify Florence and the many Medici lands and palaces. His expertise was well regarded by guildsmen and artists, who often turned to him for advice as well as for patronage